Photooxidation by Photosystem II of Tris-washed Chloroplasts - Yamashita, Takashi (1969)
Irradiation of tris-washed chloroplasts with moderate intensities of red light caused a partial bleaching of chloroplast pigments and an inhibition of the hydroquinone-supported photoreduction of NADP. The presence of an electron donor for photosystem 2 (PS2) during the irradiation prevented the bleaching and inhibition. It is concluded that the strong oxidant produced by PS2 accumulates in tris-washed chloroplasts during irradiation and an electron donor for PS2 protects against the photooxidation reactions.